Challenges for (re)building institutional trust in post-covid european territorial cooperation programmes - Medeiros, E. (Cross-border review yearbook 2021, 2021)
In my almost 30 years of academic experience in following the former EU Interreg Community Initiative, latter on (2007) transformed into one of the main EU Cohesion Policy goals (European Territorial Cooperation). I have heard and read countless times, in international events and publications, many stating the importance of ‘institutional trust’ to consolidate territorial and, in particular, cross-border cooperation institutional processes. Conversely, a few have remembered how fragile, erroneous and ephemeral is ‘institutional trust’, since it is often dependent on the individual leading this process. Here, it is common to see frequent changes in Interreg programmes’ leadership and key staff members, as well as local and regional institutional leadership with often different perspectives on how to establish cross-border and transnational cooperation processes. In this context, it goes without saying that ‘institutional trust’, if regarded as an essential counterpart of territorial cooperation, adds an extra layer of complexity to this proces s, thus requiring an insightful examination of its concrete relevance and impacts in boosting or hindering territorial cooperation in all its forms. This is the challenge we propose to discuss in this chapter, which launches the hypothesis that European Territorial Cooperation programmes (Interreg) can play a vital role in rebuilding institutional trust in European crossborder regions, which was greatly affected by the current COVID-19 pandemic.